1991
DOI: 10.1128/iai.59.10.3451-3462.1991
|View full text |Cite
|
Sign up to set email alerts
|

The immunodominant outer membrane antigen of Actinobacillus actinomycetemcomitans is located in the serotype-specific high-molecular-mass carbohydrate moiety of lipopolysaccharide

Abstract: Most patients with juvenile periodontitis manifest serum antibodies, sometimes at very high titers, to antigens of ActinobaciUus actinomycetemcomitans, but the antigens inducing the immune response have been only partly characterized. We separated A. actinomycetemcomitans serotype b cells into protein, lipopolysaccharide (LPS), and soluble polysaccharide fractions and characterized them. Coomassie blueand silver-stained sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels were used to detect protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 33 publications
6
80
3
Order By: Relevance
“…Antibodies to A. actinomycetemcomitans leukotoxin in the serum of patients with periodontitis have been previously assessed in gravimetric units only by Califano et al (1997) and at levels comparable to those reported here. To obtain leukotoxin free of contaminating lipopolysaccharide, which is an immunodominant antigen of A. actinomycetemcomitans (Page et al, 1991;Lu et al, 1993), these authors adopted a complicated assay based on the use of leukotoxin antigen in the form of bands in Western blots (Calif-ano et al, 1997). In the present study this problem was solved by the use of purified leukotoxin free of lipopolysaccharide as demonstrated by a sensitive immunochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to A. actinomycetemcomitans leukotoxin in the serum of patients with periodontitis have been previously assessed in gravimetric units only by Califano et al (1997) and at levels comparable to those reported here. To obtain leukotoxin free of contaminating lipopolysaccharide, which is an immunodominant antigen of A. actinomycetemcomitans (Page et al, 1991;Lu et al, 1993), these authors adopted a complicated assay based on the use of leukotoxin antigen in the form of bands in Western blots (Calif-ano et al, 1997). In the present study this problem was solved by the use of purified leukotoxin free of lipopolysaccharide as demonstrated by a sensitive immunochemical assay.…”
Section: Discussionmentioning
confidence: 99%
“…OMP pro¢les have shown antigenic heterogeneity among di¡erent subtypes of non-typeable H. in£uenzae [15], and most non-typeable H. in£uenzae strains possess unique outer membrane patterns compared with those of typeable strains [16]. The typeability of H. in£uenzae, reacting with antisera speci¢c for capsular types [31], however, di¡ers from serotypeability of A. actinomycetemcomitans, reacting with antisera against carbohydrate cellsurface antigens [7].…”
Section: Discussionmentioning
confidence: 99%
“…The serotype b-speci¢c antibody binding to A. actinomycetemcomitans is mediated through lipopolysaccharide (LPS) O-antigen [7,8]. Characterization of the LPS Opolysaccharide and its unique chemical composition in each of the reference strains representing all ¢ve A. actinomycetemcomitans serotypes support the view that serotype-speci¢c antigens of A. actinomycetemcomitans are localized in this O-antigenic polysaccharide of LPS in all serotypes [9,10].…”
Section: Introductionmentioning
confidence: 92%
“…Smooth LPS, which possesses O-antigen polysaccharide, is more hydrophilic than rough LPS. Some study groups think that SPA of A. actinomycetemcomitans is LPS O-antigen (21)(22)(23), and that SPA occurs as a highmolecular-weight smear that is not easily visualized by silver staining of SDS-PAGE gels. To evaluate involvement of hydrophilic O-antigen in the physical state of LPS aggregates and generation of AP-LPS, the SPAs in detergent phase and aqueous phase were compared by Western blot assay using polyclonal rabbit antiserum raised against A. actinomycetemcomitans serotype a (Fig.…”
Section: Involvement Of Lipopolysaccharide Structure In Generation Ofmentioning
confidence: 99%
“…Its strains are classified into seven serotypes (a-g), based on structurally and immunologically distinct SPAs (17)(18)(19)(20). Although there is a consensus that A. actinomycetemcomitans SPA is a polysaccharide, whether it is an O-antigen of LPS (21)(22)(23) or capsular polysaccharide (24,25) is controversial. Moreover, it remains unclear if any serotypes or stains of A. actinomycetemcomitans are able to produce stabilized LPS aggregates.…”
mentioning
confidence: 99%